Determination of Fowler–Nordheim tunneling parameters in Metal–Oxide–Semiconductor structure including oxide field correction using a vertical optimization method. (August 2016) - Toumi, S.; Ouennoughi, Z.; Strenger, K.C.; Frey, L.
Highlights: A vertical optimization process on the current density enables extraction of the FN parameters like the electron/hole effective mass in oxide mox and in semiconductor msc, the barrier height at the semiconductor–oxide interface ϕB, and the correction oxide voltage Vcorr, without any preceding assumption about ϕB and msc . FN plots calculated with three and four FN extracted parameters are in good agreement with the experimental FN plots compared to the graphical method. Abstract: Current conduction mechanisms through a Metal–Oxide–Semiconductor structure are characterized via Fowler–Nordheim (FN) plots. The extraction of the FN parameters like the electron/hole effective mass in oxide mox and in semiconductor msc, the barrier height at the semiconductor–oxide interface ϕB, and the correction oxide voltage Vcorr for a MOS structure is made using a vertical optimization process on the current density without any assumption about ϕB or mox . An excellent agreement is obtained between the FN plots calculated with the FN parameters extracted using a vertical optimization process with the experimental one.